Environmentalization as a Strategic Determinant of Construction Enterprises' Competitiveness in the Context of Global Development - Zhyshko, Roman; Ivanytsky, Ihor (Global Prosperity, 2026)
The article substantiates greening as a strategic determinant of the competitiveness of construction enterprises in the context of global development. The study is based on the premise that increasing environmental challenges, the tightening of international environmental regulations, and the growing importance of sustainable development principles significantly transform approaches to enterprise management in the construction sector. The purpose of the research is to justify the role of greening in ensuring long-term competitive advantages and to determine key directions for its integration into the strategic management system of construction enterprises. The essence of greening is defined as a comprehensive transformation of production, technological, organizational, and managerial processes aimed at achieving a balance between economic efficiency and environmental sustainability. The study reveals the multidimensional impact of greening on competitiveness, including cost reduction through resource efficiency, improvement of product quality, enhancement of corporate reputation, and increased investment attractiveness. The main global trends in the construction industry are analyzed, such as the implementation of ESG principles, circular economy, digitalization, and the development of green construction. Based on the research, key strategic directions are identified, including the integration of environmental goals into strategic management, development of eco-innovations, improvement of resource efficiency, formation of environmental corporate culture, and adaptation to international environmental standards. The scientific novelty lies in the development of a conceptual model for integrating greening into the strategic management system, which ensures the transformation of environmental factors into sustainable competitive advantages.